In-vitro Antioxidant and Anti-Inflammatory Activities of Peel and Peeled Fruits Citrus limon - Basli, Abdelkader; Sonia, Tighzert; Nawel, Ibelhoulen; Bachra, Khettal; Khodir, Madani (Current Nutrition & Food Science, 2016)
Background: Citrus is the name given to trees belonging to the family of Rutaceae including several species of plants that produce the edible fruits providing an appreciable content of several interesting bioactive constituents. In traditional medicine, they are often used as antipyretic, anti-inflammatory, sedative and antitoxic agents. Our primary aim is to assess antioxidant ability and anti-inflammatory activity of peel and peeled fruit from Citrus limon. Methods: Ethanolic extracts of peel and peeled fruit of Citrus limon (lemon) were used to investigate antioxidant and anti-inflammatory activities. Total phenolic content was assessed using Folin-Ciocalteux method. The antioxidant potential was found by measuring the scavenging activity of DPPH and ABTS radical. Three methods have been adopted to evaluate in-vitro anti-inflammatory effect by bovine albumin denaturation, lipoxygenase inhibition and erythrocytes membrane stabilization. Diclofenac as a reference control drug has been used for the study of anti-inflammatory activity. Results: Peels of lemon revealed significantly highest total phenolic content than peeled fruit fraction. Two parts of lemon have shown potent scavenging activity in both DPPH and ABTS methods. Peels and peeled fruit exhibited a significant maximum inhibition of protein denaturation with concentration dependent inhibition manner. The hypotonicity induced haemolysis as well as the antilipoxygenase activities of two parts of lemon has proved significant inhibition at the concentration range of 100-500μg/mL. Likewise, diclofenac showed the highest inhibition for all anti-inflammatory assays. Conclusion: Peel and peeled fruit of Citrus limon extracts can be an important source of anti-inflammatory agents.
Keywords: Peel and peeled fruit of Citrus limon extracts can be an important source of anti-inflammatory agents